De historias y memorias sobre el pasado reciente en Uruguay: treinta años de debates - Eugenia Allier Montaño (Caravelle)
For many years, social sciences have been aware of souvenir’s importance in those countries which have known a violent recent past. Uruguay, emerging from a civic and military dictatorship n 1985, has gone through several periods and transformations concerning the memories related to this recent past. First of all, in this article we analyze and give them a historical dimension. Then we examine the forms which permitted this recent past to acquire such a dimension.